2016
DOI: 10.1002/celc.201600219
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X‐ray Tomographic Study of a Silicon Electrode Before and After Discharge and the Effect of Cavities on Particle Fracturing

Abstract: Silicon (Si) has been proposed as one of the most promising anode materials for next-generation lithium ion batteries (LIBs). However, unsatisfactory discharge capacity/energy density and inevitable performance worsening prevent their commercialization. Herein, an in-depth investigation on the same Si composite electrode before and after the first discharge by employing in situ synchrotron X-ray tomography is presented. It is found that i) on the electrode level, the Si particles located in the central part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…The peaks at 2θ=21.0°, 28.5°, 56.1° were all ascribed to that of silica. However, they still had many differences, where the peak at 2θ=47.5° indicated the presence of crystal silicon while the peaks at 2θ=26.5°, 44.5°, 50.5°, 60.1° were assigned to characteristic peaks of graphite, which suggested an amount of layered structure carbon was formed . In order to confirm the existing form of silicon, X‐ray photoelectron spectroscopy was conducted to MSBC and the results are plotted in Figure S1 and Figure S2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The peaks at 2θ=21.0°, 28.5°, 56.1° were all ascribed to that of silica. However, they still had many differences, where the peak at 2θ=47.5° indicated the presence of crystal silicon while the peaks at 2θ=26.5°, 44.5°, 50.5°, 60.1° were assigned to characteristic peaks of graphite, which suggested an amount of layered structure carbon was formed . In order to confirm the existing form of silicon, X‐ray photoelectron spectroscopy was conducted to MSBC and the results are plotted in Figure S1 and Figure S2.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Figure a, statistical analyses showed that the size of the MSBC particles varied from 0.06 to 42.25 μm with an average diameter (D50) of 7.83 μm. Such size distribution is among the preferred range for electrode fabrication and is beneficial for compaction of materials and producing high density commercial LIBs . Figure b is the N 2 adsorption/desorption isotherms of the MSBC particles at 77 K, which displayed a typical IV isotherm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present work focuses on monitoring the SE in contact with the Na metal anode during cycling and aims to derive practical guidelines for long‐term stable operation. First, cells with Na metal anode and liquid electrolyte are cycled and investigated with in situ synchrotron X‐ray tomography (similar method as reported elsewhere) and with ex situ surface analytic methods to assess the deleterious effects of dendrite formation as a reference case. Then, Na‐β‐alumina is introduced to protect the electrodes during cycling.…”
Section: Introductionmentioning
confidence: 99%